Analisis Pemasaran Hasil Tangkapan Jaring Insang Di Desa Linsowu Kecamatan Kulisusu Kabupaten Buton Utara - Ardin; Budiyanto; Riani, Irdam; Abdullah; Sriwulan, Desy (Jurnal Sosial Ekonomi Perikanan, 2023)
This research objectives are (a) to know the marketing channels of gill net catches. (b) knowing the marketing margin of gill net catch. (c) knowing the marketing efficiency of gill net catches. The population in this study were 10 fisherman with gill nets, while the sample was taken using the snowball sampling methods on 5 fisherman who were marketing actors. Data obtained through observation, interviews and documentation. The data analysis used is (1) quantitative descriptive analysis, (2) margin analysis and (3) marketing efficiency analysis. The results showed that: (1) the fish marketing channel in Linsowu Village there are 2 marketing channels, channel I fisherman – consumers, channel II fisherman - diluent traders - consumers. (2) The marketing margin of the gill net catch is in channel II of IDR.5000. (3) Efficiency of marketing channels for gill net catches is 75% and 100% (criteria > 50 efficient).